Telematics and computing : 7th International Congress, WITCOM 2018, Mazatlán, Mexico, November 5-9, 2018, Proceedings /: 7th International Congress, WITCOM 2018, Mazatlán, Mexico, November 5-9, 2018, Proceedings. (2018) - Unknown
No abstract available